x=35
In order to solve this equation you need to know what -28x-2 equals. If you were to assume it was 0 then x = 0.071 rounded
.740
7x+7=28x 28x-7x=7 21x=7 x=3
68 + 28x - 28 = 236 28x + 68 - 68 -28 + 28 = 236 - 68 + 28 28x = 196 x = 7
x=1/3,3/5
8x-17=6x+112x=28x=14
49x2+28x+4 = (7x+2)(7x+2) when factored
3x + 5x = 2x + 28x = 2x + 26x = 2x = (2/6) = 1/3
4x + (28x -2) is not an equation. It doesn't ask a question, so it doesn't need answering or solving. The expression stands for a number. In order to know the number, you first have to know what number 'x' is.
The sum is 28x
what is -12X squared +28X - 15? i figured it out myself. its (-6X + 5)(2X - 3).
5x + 23x + 10 = 28x + 10( ? ? ? )